Outside over there - Sendak, Maurice; Wong, Jeanyee ([New York] : HarperCollins, 1981)
While her papa is off at sea, goblins come in and steal Ida's baby sister; and now she must try to rescue her.
Illustrated by the author.
"An Ursula Nordstrom book"--T.p. verso.
Wilson's Children, June 2001
Notable/Best Books (A.L.A.), November 2008
Booklist, October 2008
Bulletin (Center for Children's books), April 2008
Keywords: Sisters -- Fiction; Fantasy; Sisters -- Fiction; Fantasy fiction